Study of Bacillus megaterium potential application for high metal content residues biotreatment - Andrea M Rivas-Castillo; Yessica Mejía-Escobedo; Norma G Rojas-Avelizapa (Open Journal of Bacteriology - Peertechz Publications, 2018)
Previous work has demonstrated that Bacillus megaterium, besides showing an elevated resistance to heavy metals, possesses the ability to remove metals like Ni, Hg, and V from liquid media. Notably, Ni represents a highly valuable metal commonly found in industrial wastes, whose removal from environment is crucial, as it is considered a dangerous toxic metal. Thus, the aim of the present study was to determine Bacillus megaterium MNSH1-9K-1 resistance to Al, Ni, V, and Mo, metals that are commonly found in high metal content residues, and also evaluate its Ni removal capability from liquid medium. To this end, the microorganism was exposed to different metal concentrations, and its resistance was assayed by serial dilutions and viable count. Afterwards, MNSH1-9K-1 Ni resistance and removal capability was evaluated by ICP-OES. The results showed that this microorganism presents a Minimum Inhibitory Concentrations of 240, 2000, 35000 and >270000 ppm for Ni, Al, V, and Mo, respectively. Even more, MNSH1-9K-1 is able to remove up to 26 ppm of Ni. The results presented here may contribute to the knowledge regarding the application of this microorganism for the biotreatment of high metal content liquid and solid residues, mainly the ones containing Ni.